Cancer immunometabolism: advent, challenges, and perspective - Qin Dang; Borui Li; Bing Jin; Zeng Ye; Xin Lou; Ting Wang; Yan Wang; Xuan Pan; Qiangsheng Hu; Zheng Li; Shunrong Ji; Chenjie Zhou; et al. (Molecular Cancer, 2024)
Abstract For decades, great strides have been made in the field of immunometabolism. A plethora of evidence ranging from basic mechanisms to clinical transformation has gradually embarked on immunometabolism to the center stage of innate and adaptive immunomodulation. Given this, we focus on changes in immunometabolism, a converging series of biochemical events that alters immune cell function, propose the immune roles played by diversified metabolic derivatives and enzymes, emphasize the key metabolism-related checkpoints in distinct immune cell types, and discuss the ongoing and upcoming realities of clinical treatment. It is expected that future research will reduce the current limitations of immunotherapy and provide a positive hand in immune responses to exert a broader therapeutic role.